THE NEXUS OF FINANCIAL LITERACY, FINANCIAL TECHNOLOGY, AND FINANCIAL INCLUSION ON FINANCIAL PERFORMANCE: INSIGHTS FROM LAMONGAN'S CULINARY MSMES - Maulidia Putri, Ihza Zamzara; Rachmaniyah, Fatichatur; Shoimah, Siti (DIVERSITY Logic Journal Multidisciplinary, 2024)
Background: The MSME culinary sector is one of the most popular industries in Indonesia, particularly in Lamongan. MSME entrepreneurs in this sector need to enhance their understanding of financial literacy and financial inclusion to improve their business's financial performance. Additionally, keeping up with modern developments by utilizing financial technology is crucial to optimizing financial management. Research Purpose: This study aims to understand how financial literacy, fintech, and financial inclusion impact the financial performance of culinary micro, small, and medium enterprises in Lamongan. Research Method: This study uses an explanatory quantitative research approach. Data collection was conducted through Likert-scale questionnaires distributed to 140 MSME respondents in the culinary sector in Lamongan. These respondents were selected using purposive sampling, and the data were analyzed using multiple linear regression. Findings: The study reveals that financial literacy and inclusion enhance the financial performance of culinary micro, small, and medium enterprises in Lamongan. While fintech's role is insignificant, a synergistic approach involving all three factors significantly contributes to improved performance. Conclusion: Financial literacy and financial inclusion among MSMEs in Lamongan's culinary sector are relatively good. However, the application of financial technology does not significantly affect financial performance, as most consumers in Lamongan, from lower-middle-income groups, do not widely use fintech for transactions.